Bioanalytical System for Determining the Phenol Index Based on Pseudomonas putida BS394(pBS216) Bacteria Immobilized in a Redox-Active Biocompatible Composite Polymer “Bovine Serum Albumin–Ferrocene–Carbon Nanotubes” - Perchikov, Roman N.; Provotorova, Daria V.; Kharkova, Anna S.; Arlyapov, Vyacheslav A.; Medvedeva, Anastasia S.; Machulin, Andrey V.; Filonov, Andrey E.; Reshetilov, Anatoly N. (Polymers, 2022)
The possibility of using the microorganisms Pseudomonas sp. 7p-81, Pseudomonas putida BS394(pBS216), Rhodococcus erythropolis s67, Rhodococcus pyridinivorans 5Ap, Rhodococcus erythropolis X5, Rhodococcus pyridinivorans F5 and Pseudomonas veronii DSM 11331T as the basis of a biosensor for the phenol index to assess water environments was studied. The adaptation of microorganisms to phenol during growth was carried out to increase the selectivity of the analytical system. The most promising microorganisms for biosensor formation were the bacteria P. putida BS394(pBS216). Cells were immobilized in redox-active polymers based on bovine serum albumin modified by ferrocenecarboxaldehyde and based on a composite with a carbon nanotube to increase sensitivity. The rate constants of the interaction of the redox-active polymer and the composite based on it with the biomaterial were 193.8 and 502.8 dm3/(g·s) respectively. For the biosensor created using hydrogel bovine serum albumin-ferrocene-carbon nanotubes, the lower limit of the determined phenol concentrations was 1 × 10−3 mg/dm3, the sensitivity coefficient was (5.8 ± 0.2)∙10−3 μA·dm3/mg, Michaelis constant KM = 230 mg/dm3, the maximum rate of the enzymatic reaction Rmax = 217 µA and the long-term stability of the bioanalyzer was 11 days. As a result of approbation, it was found that the urban water phenol content differed insignificantly, measured by creating a biosensor and using the standard photometric method.